2020
DOI: 10.1111/jcmm.16146
|View full text |Cite
|
Sign up to set email alerts
|

COPD patients with chronic bronchitis and higher sputum eosinophil counts show increased type‐2 and PDE4 gene expression in sputum

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 76 publications
(150 reference statements)
2
11
0
1
Order By: Relevance
“…A recent study identifying SOCS2 and HDC as differentially expressed in E-COPD vs NE-COPD in sputum microarray analysis supports the positive association between MC/basophil genes and eosinophilic inflammation in COPD. 37 This study also reported increased IL9R in E-COPD compared to non-eosinophilic COPD. IL9 promotes MC growth and differentiation, and this further supports the role of MCs and basophils in T2 inflammation in COPD.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A recent study identifying SOCS2 and HDC as differentially expressed in E-COPD vs NE-COPD in sputum microarray analysis supports the positive association between MC/basophil genes and eosinophilic inflammation in COPD. 37 This study also reported increased IL9R in E-COPD compared to non-eosinophilic COPD. IL9 promotes MC growth and differentiation, and this further supports the role of MCs and basophils in T2 inflammation in COPD.…”
Section: Discussionsupporting
confidence: 58%
“…IL9 promotes MC growth and differentiation, and this further supports the role of MCs and basophils in T2 inflammation in COPD. 37 mRNA abundance of all MC/basophil genes was correlated in COPD sputum, supporting a common MC/basophil origin, with qPCR measures of MC/ basophil-related genes reflecting MC and basophil abundance in sputum. There were no significant clinical differences between E-COPD and NE-COPD and therefore the differences in MC/basophil gene expression between the groups demonstrate the importance of molecular biomarkers such as these to distinguish between COPD inflammatory phenotypes.…”
Section: Discussionmentioning
confidence: 62%
“…In line with these observations the ability of tanimilast to reduce eosinophils and other key type-2 mediators in sputum (e.g. IL5RA, CLC, ALOX15, SMPD3, PTGDR2, and CEBPE) was most relevant to individuals with higher sputum eosinophil counts (≥3%) ( Singh et al, 2020d ; 2020b ). These data are in line with the reduction of sputum and bronchial mucosal eosinophils observed in patients treated with roflumilast ( Rabe et al, 2018 ) and support the rationale for PDE4 inhibition on top of inhaled corticosteroids and bronchodilators also in patients with higher eosinophil counts.…”
Section: Clinical Overviewsupporting
confidence: 62%
“…In patients with chronic bronchitis, tanimilast administered on top of ICS, a LABA and a LAMA consistently reduced a large number of key mediators associated to airways inflammation, remodeling and lung integrity ( Singh et al, 2019 ; Govoni et al, 2020 ). Notably, patients treated with triple therapy and having higher eosinophil counts at baseline (and thus patients known to respond better to ICS) showed increased levels of sputum cell inflammation associated to type-2 and PDE4 mediators ( Singh et al, 2020b ). These findings supported the potential for tanimilast to provide an additional beneficial effect in patients with chronic bronchitis who are still symptomatic despite regular use of ICS, LABA and LAMA, with a favorable systemic tolerability profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation